Efektifitas Edukasi Berbasis Audiovisual Dan Tutorial Tentang Arv Terhadap Kepatuhan Pada Pasien Odha Di Puskesmas Bandarharjo - Iq Balurrochman; Rahayu Winarti; Maulidta K.W (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Non-adherence to antiretroviral therapy (ART) among people living with HIV/AIDS (PLWHA) remains a critical challenge that exacerbates treatment failure and viral resistance. This study aimed to compare the effectiveness of audiovisual-based and instructional-structured tutorial education on medication adherence among PLWHA at the Bandarharjo Community Health Center. A quasi-experimental study with a two-group pretest-posttest design was conducted using a purposive sample of 26 active PLWHA undergoing ART. Data analyzed using the Wilcoxon signed-rank and Mann-Whitney U tests revealed significant post-intervention improvements in both groups (p = 0.000). However, the comparative analysis of posttest outcomes showed no statistically significant difference between the two modalities (p = 0.650 > 0.05), indicating clinical equivalence. Conclusion: Both interventions exhibit equivalent efficacy in optimizing ART adherence, providing public health practitioners at primary care levels with operational flexibility based on resource availability.